The use of the Family Management Style Framework to evaluate the family management of liver transplantation in adolescence - Ana Márcia Chiaradia Mendes-Castillo; Regina Szylit Bousso; Carolliny Rossi de Faria Ichikawa; Luciana Rodrigues Silva (SciELO, 2014)
Objective: To understand the family management experience of liver transplantation during adolescence based on the Family Management Style Framework(FMSF). Method: This is a case study that used the FMSF as theoretical framework and the hybrid model of thematic analysis as methodological reference. The case presented is from an adolescent's family that lives in Salvador, Bahia. The data were collected through interviews with the mother and the patient charts analysis. Results: The results shows that the family defines the transplantation as threatening and there are divergence between mother and daughter related to the teen's capabilities perception. Facing those discrepancies, the family assumes a protective posture by believing that the teen cannot take care of herself alone. The perceived consequences reflect how much the uncertainty permeates the family environment. Conclusion: It is concluded that the use of a model to evaluate the management can help professionals to direct and plan specific interventions.